The Role of Parents in Addressing the Influence of Free Fire Game on Children's Morality in Dapu-Bata Sabang Community - Irham, Irham (International Journal Education and Computer Studies (IJECS), 2025)
The swift advancement of digital technology has transformed children’s daily lives and introduced new challenges in their moral education. This study sought to examine the effect of the Free Fire game on children’s morality at Dapu-Bata, Sabang, as well as parents’ strategies and obstacles in dealing with this problem. It used a descriptive qualitative method for data collection through observation, interviews, and documentation from parents, Free Fire-playing children, community leaders, and teachers. The results indicated that the duration of playing Free Fire influences children’s morality concerning emotional control, religious practice, study motivation, and communication with family members. There is an apparent decline in prayer frequency and motivation to study accompanied by reduced communication with parents. Out of all strategies employed to combat these effects on morality due to gaming, enhancing religious education together with building communication between parent and child plus providing alternative activities for children was found most effective among others. Difficulties faced by parents were peer pressure from friends accompanied by unrestricted internet access for kids who are addicted to games due to low digital literacy skills among them; however, this study recommends integrating Islamic educational values into parenting strategies based on empirical evidence for upholding moral education in the digital era.
Keywords: Free Fire; Children’s Morality; Parental Role; Islamic Education; Digital Era